To see or not to see the vet: A vignette-based study of decision-making by UK dog owners regarding seeking veterinary care for commonly presenting conditions - Michelle Farrow; Dan G. O’Neill; Rowena M. A. Packer (PLoS ONE, 2026)
Barriers to accessing veterinary-care for dog-owners are diverse and dynamic, and widely accepted as major canine welfare threats because of potential non-, under- or delayed treatment. Owner knowledge and perceptions are recognised as key influences on decisions to seek veterinary-care but are currently understudied. This study aimed to explore decision-making by UK dog-owners around seeking veterinary-care for common conditions in dogs and identify influences upon these decisions prior to the introduction of Artificial Intelligence technologies. An online vignette-based survey collected responses from UK dog-owners regarding disorder vignettes ( n = 3) randomly selected from a bank of n = 30, that were developed from anonymised VetCompass clinical histories to describe common canine conditions in general practice. Framed as being the dog-owner for each vignette, participants suggested (i) the condition they believed the dog was affected by, (ii) their perceived urgency for seeking veterinary-care and (iii) information-sources used to influence their decisions. Post-vignette questions explored participants’ real-world dog-health information-sourcing behaviours for their own dog(s). Outcomes modelled included (1) accuracy of condition identification, and (2) appropriateness of urgency assessments compared to consensus from a panel of veterinary surgeons. Analyses included n = 5316 vignette responses from n = 1772 participants. Epilepsy, kennel cough, flea infestation and osteoarthritis were the most accurately identified disorders whereas mast cell tumour, glaucoma and gastrointestinal foreign body were the least accurately identified. Owners using internet-searching for health-information to aid vignette responses scored higher on accuracy than those who did not. Owners perceived conditions to require veterinary-care less urgently than veterinary surgeons in 28.4% of vignette responses; however, using online dog-health groups for information-sourcing reduced the risk of under-urgency. Owners were most accurate at identifying conditions with external clinical signs but often underestimated urgency of seeking veterinary care. Improved accessibility and utilisation of veterinary triage services, telemedicine and information-prescriptions for owners could improve canine welfare by supporting better dog-owner decision-making and optimising veterinary professional workload.